Screening for post‐traumatic stress disorders in 1017 cancer patients and correlation with anxiety, depression, and distress. Issue 12 (3rd November 2019) - Unseld, Matthias; Krammer, Katharina; Lubowitzki, Simone; Jachs, Mathias; Baumann, Lukas; Vyssoki, Benjamin; Riedel, Jasmin; Puhr, Hanna; Zehentgruber, Stefan; Prager, Gerald; Masel, Eva Katharina; Preusser, Matthias; et al.
Abstract: Objective: Post‐traumatic stress disorder (PTSD) is a severe psychiatric disorder, which might develop after a traumatic event, like cancer diagnosis, and threatens the patient's psychological and/or physiological integrity. Anxiety, depression, and mental distress are known to be common in cancer patients; however, the frequency of PTSD was not investigated thoroughly in this patient group so far. Here, we aim to screen cancer patients for PTSD symptoms and determine a possible correlation with anxiety, depression, and distress. Methods: The study was performed at the Divisions of Hematology and Oncology of the Medical University of Vienna from 2010 to 2018. Following written consent, patients were asked to fill out the validated self‐assessment questionnaire for PTSS‐10 and HADS. The study was approved by the institutional ethics committee of the Medical University of Vienna (EC Nr: 2255/2016). Results: A total of 1017 adult cancer patients (513 male, 504 female) were included in a cross‐sectional single‐center study. Mean age was 57.6 years (SD 14.4 years); 31.7%, 14.6%, 13.2%, and 27.4% of patients outscored the predefined thresholds for self‐assessed cases of PTSD, anxiety, depression, and distress, respectively. Compared with men, women showed a higher prevalence of symptoms for PTSD (38.9% vs 24.5%; P < .001) and anxiety (20.4% vs 8.6%; P < .001). The scores of HADS‐A, HADS‐D, and the combined HADS score (distress) were significantly correlated with PTSS‐10 scores ( P < .01). No differences in age were observed among the different score groups. Conclusion: The study shows a significant prevalence as well as a correlation of PTSD symptoms with anxiety, depression, and distress among cancer patients. Findings underscore the necessity of a serious screening for psychiatric disorders, especially in female patients. In order to enable multidisciplinary care for cancer patients and to reduce the burden for psychiatric disorders, interdisciplinary screening and treatment concepts, which take into account gender aspects, are urged.